MONTESSORI TEACHING METHODS ENGLISH (Ustozlar uchun, 2025)
This article explores the benefits of using the Montessori  Method to teach English in elementary grades. The Montessori approach,  known for its emphasis on self-directed learning and hands-on activities, offers  a unique and effective way to foster language acquisition skills among young  learners. By creating an engaging and interactive environment, students can  develop a solid foundation in English while also nurturing their creativity and  independence.